2005
DOI: 10.1007/s00428-004-1176-0
|View full text |Cite
|
Sign up to set email alerts
|

A second field metachronous Merkel cell carcinoma of the lip and the palatine tonsil confirmed by microarray-based comparative genomic hybridisation

Abstract: Merkel cell carcinoma was diagnosed in a 79-year-old Caucasian woman. The tumour was localised to the upper lip and was in stage T2. After successful cryosurgery and a 7-year tumour-free period, a new tumour developed in her palatine tonsil. Histologically and immunohistochemically, this resembled the tumour in the lip. The regional lymph nodes were devoid of metastasis. The paraffin-embedded material of the two tumours and the unaffected lymphatic tissue were analysed with DNA microarrays for comparative geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…Regarding the assessment of the therapeutic efficacy of immunocryosurgery in MCC, topical imiquimod has been evaluated in a single case of MCC in combination with radiotherapy (12) and complete remission for 7 years of a primary T2 MCC was described with cryosurgery (13). Before the observed therapeutic outcome can be ascribed to immunocryosurgery one should consider the possibility of spontaneous regression.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the assessment of the therapeutic efficacy of immunocryosurgery in MCC, topical imiquimod has been evaluated in a single case of MCC in combination with radiotherapy (12) and complete remission for 7 years of a primary T2 MCC was described with cryosurgery (13). Before the observed therapeutic outcome can be ascribed to immunocryosurgery one should consider the possibility of spontaneous regression.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have only been 3 studies to date that have used genomic analysis to investigate the relationship between multiple cutaneous MCCs 6, 7, 8. Nagy et al 7 used aCGH to show that although MCCs of the lip and palatine tonsil, separated in time by 7 years, showed 31 distinct copy number alterations, they did not arise independently, as they shared copy number changes at 45 other chromosomal loci 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Kaae et al (16) reported a statistically significant increased risk of squamous cell carcinoma of the skin and chronic lymphocytic leukaemia after a diagnosis of MCC. As MCC is a rare tumour, it is unknown whether there is an increased (18). Our patient represents the first case of a metachronous MCC arising in the same organ (facial skin).…”
Section: Discussionmentioning
confidence: 79%